Futsal task constraints promote transfer of passing skill to soccer task constraints. Issue 7 (9th August 2018) - Oppici, Luca; Panchuk, Derek; Serpiello, Fabio Rubens; Farrow, Damian
Abstract: This study investigated how learning a passing skill with futsal or soccer task constraints influenced transfer to a new task. Futsal ( n = 24, 13.6 ± 1.2 years old, 7.0 ± 1.6 years of experience) and soccer ( n = 24, 13.6 ± 1.2 years old, 6.8 ± 1.2 years of experience) players performed two 5v5 + goalkeeper modified games – a futsal-like task (small playing area with the futsal ball) and soccer-like task (large playing area with the soccer ball). Participants' passing accuracy and their orientation of attention were assessed during the two tasks. The futsal group improved their passing accuracy (ES = 0.75 ± 0.61) from the futsal-like to the soccer-like task, and they were more accurate than soccer players (ES = 2.98 ± 2.96). Conversely, the soccer group's passing accuracy remained stable across the two tasks (ES = 0.10 ± 0.52) and it was similar to the futsal group in the futsal-like task (ES = 0.58 ± 1.93). This indicates a higher magnitude of transfer (and adaptability) from performing passes in a small playing area with short time to act – futsal task constraints – to a larger playing area with longer time – soccer task constraints – than vice-versa. Furthermore, the futsal group showed a higher adaptation of attention orientation to the affordances that emerged with the soccer task constraints, which is suggested to be one of the main mechanisms promoting skill transfer. These results encourage soccer practitioners to introduce futsal task constraints to fast-track players' ability to functionally adapt perception–action coupling.